1993
DOI: 10.1259/dmfr.22.2.8375559
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two registration techniques for digital subtraction radiography.

Abstract: The dental radiograph is a diagnostic tool that is used to view internal structures without any invasive procedures. A difference radiograph, i.e. one showing the changes that occurred over time, is the best tool for diagnosing slow or small changes. The difficulty in creating a meaningful difference radiograph, or its digital image, is that the imaging geometry of the image pair must be identical. This paper addresses the problem of reproducing imaging geometry. A new technique for registering digital images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 2 publications
0
14
0
3
Order By: Relevance
“…This was rejected on ethical grounds. In a previous study, however, Dunn et al 9 made double exposures from volunteers. They showed that the mathematical technique as implemented in the Emago/Advanced software that we applied, can be used to establish correspondence between pairs of clinical images taken at dierent projection angles and to produce reconstructed images comparable with images taken with occlusal stents.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This was rejected on ethical grounds. In a previous study, however, Dunn et al 9 made double exposures from volunteers. They showed that the mathematical technique as implemented in the Emago/Advanced software that we applied, can be used to establish correspondence between pairs of clinical images taken at dierent projection angles and to produce reconstructed images comparable with images taken with occlusal stents.…”
Section: Discussionmentioning
confidence: 98%
“…This procedure was repeated for each of the 50 radiographs. Emago used the reconstruction algorithm described by Dunn et al 9 to identify the co-ordinates of each pixel of the ®rst image in the second image. The second image was reconstructed and subtracted from the initial image using linear subtraction.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In the early 1980s, new software applications for DSR were introduced with reconstruction algorithms to derive a plain image with approximate geometric projection of a reference image obtained at a different geometric configuration. Geometric image reconstruction in DSR is based on the principle developed by Dunn et al, 5 who applied mathematical equations to find coordinates of corresponding points of a reference image in a secondary image. This results in a stable alignment between pairs of points and improves the performance of DSR.…”
Section: Introductionmentioning
confidence: 99%